2023
DOI: 10.1186/s13244-023-01365-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with radiomics quality score of cholangiocarcinoma: an EuSoMII Radiomics Auditing Group Initiative

Abstract: Objectives To systematically review current research applications of radiomics in patients with cholangiocarcinoma and to assess the quality of CT and MRI radiomics studies. Methods A systematic search was conducted on PubMed/Medline, Web of Science, and Scopus databases to identify original studies assessing radiomics of cholangiocarcinoma on CT and/or MRI. Three readers with different experience levels independently assessed quality of the studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Upon comparison with radiomics meta-analyses in other fields, we observed that the quality of radiomics studies is a widely concern. For instance, a review of cholangiocarcinoma encompassing 38 original studies reported a median RQS of 9, amounting to just 25.0% of the total RQS ( 52 ). Similarly, a review focusing on ovarian imaging, which included 63 studies, found a median RQS of 6, corresponding to 30.6% of the total RQS, indicating lower scoring ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon comparison with radiomics meta-analyses in other fields, we observed that the quality of radiomics studies is a widely concern. For instance, a review of cholangiocarcinoma encompassing 38 original studies reported a median RQS of 9, amounting to just 25.0% of the total RQS ( 52 ). Similarly, a review focusing on ovarian imaging, which included 63 studies, found a median RQS of 6, corresponding to 30.6% of the total RQS, indicating lower scoring ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in study populations, methodologies, and the choice of utilizing first-pass effect recirculation results or multiple recirculation results for predicting MTB also could contribute to the inter-study heterogeneity. Indeed, previous studies have emphasized that radiomics studies are heterogeneous in various areas ( 52 55 , 59 , 61 , 62 ). Subgroup analysis may partially address this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review about cholangiocarcinoma, the highest RQS was 18, and there were only 7 studies (18.4%) with ≥ 15 scores. Thirty (79.0%) studies were performed at one institution, and all the included studies were conducted retrospectively [ 44 ]. For our study, patients from two centers were included retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…For our study, patients from two centers were included retrospectively. Moreover, the most common study aims included differential diagnosis against other hepatic lesions, prediction of survival after surgical resection, prediction of lymph node metastases, and prediction of therapeutic response to radioembolization [ 44 ]. Currently, none of the studies covered the prediction of TLSs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inter-reader variability and reproducibility of the radiomics features are crucial for the validation of the radiomics model, and they are often missing in current studies. A recent systematic review pointed out that the methodological rigor and quality of radiomics studies are still unsatisfactory in ovarian pathologies, with a reported radiomics quality score of 6, corresponding to 16.7% of the total score, which is lower compared with other fields of research in radiomics studies [169][170][171].…”
Section: Mrimentioning
confidence: 99%